The synthesis of porous ultrathin graphitic carbon nitride for the ultrasensitive fluorescence detection of 2, 4, 6-trinitrophenol in environmental water. Issue 1 (13th December 2019) - Qu, Binhong; Mu, Zhiyuan; Liu, Yang; Liu, Yingsha; Yan, Rui; Sun, Jianhui; Zhang, Zishu; Li, Peng; Jing, Liqiang
Abstract : The porous ultrathin g-C3 N4 nanosheets with strong adsorption capacity have been synthesized for the ultrasensitive fluorescence detection of 2, 4, 6-trinitrophenol in water by the frequently neglected double-logarithmic Stern–Volmer equation. Abstract : The ultrasensitive detection of 2, 4, 6-trinitrophenol (TNP) for environmental security is important but challenging. Graphitic carbon nitride (g-C3 N4 ) is promising for the fluorescence sensing of TNP. It is highly desired to greatly promote the adsorption of TNP onto g-C3 N4 for improving the fluorescence detection sensitivity. Herein, porous ultrathin g-C3 N4 (∼1.3 nm) nanosheets were successfully synthesized via combining second calcination with HNO3 treating processes. Under the optimized conditions of the excitation wavelength (Ex = 350 nm) and solution pH value (pH = 3), the wide detection range of TNP from 4 μM to 54 μM was confirmed by the widely adopted normal Stern–Volmer equation (SVE). Interestingly, the limit of detection was as low as 0.04 nM according to the linear range from 0.1 nM to 4 μM by the generally neglected double logarithmic (DL) SVE, which is much competitive for TNP detection compared with previously reported results. Based on the isothermal adsorption curves and the time-resolved fluorescence and surface photovoltage spectra, it was confirmed that the multilayer adsorption of TNP on the resulting g-C3 N4 at low concentrations mainly led to fluorescence quenching by the inner filter effect (IFE), while the monolayer adsorption at ultralow concentrations resulted in fluorescence quenching by the combined effects of IFE and photoinduced electron transfer. It was suggested that normal and DL SVEs are applicable to the fluorescence quenching processes determined by single and double factors, respectively. The obtained ultrasensitive detection was attributed to the greatly promoted adsorption of TNP via hydrogen bonding by enlarging the surface area from the porous nanosheet structure and by increasing the surface –OH sites from the HNO3 treatment. This work helps to deeply understand SVE related to the fluorescence quenching processes and provides a feasible route to develop a method for the ultrasensitive detection of TNP with g-C3 N4 nanosheets for environmental water monitoring and security inspection.